Stabilisasi Harga Pangan Nonberas di Malaysia (Forum Penelitian Agro Ekonomi, 2016)
EnglishMalaysian Government applies policy on non-rice price stabilization through farmers’ product purchase, incentives for farmers, and retail price control. This paper aims (i) to review Malaysia’s policy on food production; (ii) to assess price control and farmers’ protection policy; and (iii) to learn a lesson from Malaysia’s success in stabilizing strategic goods prices. Ministry of Domestic Trade, Co-operatives and Consumerism (MDTCC) controls strategic goods price established by Malaysian Government. Federal Agricultural Marketing Agency (FAMA) controls domestic supply of agricultural products such that the prices are feasible to farmers but affordable to consumers. Ministry of Agriculture Indonesia could learn from success of this neighboring country in protecting farmers for producing agricultural products in order to maintain domestic supply and to stabilize food price.IndonesianPemerintah Malaysia melakukan stabilisasi harga pangan nonberas melalui jaminan pembelian hasil panen petani, insentif kepada petani, dan pengendalian harga eceran. Tulisan ini bertujuan untuk (i) melakukan tinjauan kebijakan Pemerintah Malaysia dalam produksi pangan; (ii) mempelajari kebijakan pengendalian harga pangan strategis dan perlindungan bagi petani; dan (iii) mengambil manfaat dari keberhasilan Malaysia dalam mengendalikan harga produk strategis. Kementerian Dalam Negeri, Koperasi, dan Kepenggunaan (KPDNKK) Malaysia mengendalikan harga eceran kebutuhan pokok yang sudah ditentukan oleh Pemerintah Malaysia. Federal Agricultural Marketing Agency (FAMA) mengendalikan pasokan produk pertanian ke pasar domestik dengan menjaga harga dasar yang menguntungkan bagi petani tetapi masih terjangkau bagi konsumen. Kementerian Pertanian Indonesia bisa belajar dari pengalaman negara jiran tersebut untuk membantu petani agar tetap bergairah menghasilkan produk pertanian sehingga pasokan dan harga pangan relatif stabil.
Keywords: ceiling price; FAMA; farmers’ market; floor price; Malaysia; harga dasar; harga tertinggi; pasar tani